2020
DOI: 10.1002/ange.202000961
|View full text |Cite
|
Sign up to set email alerts
|

A Glutathione Activatable Ion Channel Induces Apoptosis in Cancer Cells by Depleting Intracellular Glutathione Levels

Abstract: Cancer cells use elevated glutathione (GSH) levels as an inner line of defense to evade apoptosis and develop drug resistance. In this study, we describe a novel 2,4‐nitrobenzenesulfonyl (DNS) protected 2‐hydroxyisophthalamide system that exploits GSH for its activation into free 2‐hydroxyisophthalamide forming supramolecular M+/Cl− channels. Better permeation of the DNS protected compound into MCF‐7 cells compared to the free 2‐hydroxyisophthalamide and GSH‐activatable ion transport resulted in higher cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Therefore, GSH depletion could be an effective approach for cancer therapy. Talukdar and co-workers [183] found that the T-DNS probe This was accompanied with an increase in blue fluorescence emission at 410 nm (Fig. 30).…”
Section: Fluorescent Probes For Reactive Sulfur Species (Rss)mentioning
confidence: 85%
“…Therefore, GSH depletion could be an effective approach for cancer therapy. Talukdar and co-workers [183] found that the T-DNS probe This was accompanied with an increase in blue fluorescence emission at 410 nm (Fig. 30).…”
Section: Fluorescent Probes For Reactive Sulfur Species (Rss)mentioning
confidence: 85%
“…[14][15] Talukdar has recently reported GSH switchable synthetic ion channels capable of achieving transmembrane M + /Clsymport in presence of elevated levels of GSH. [16] These systems induced caspase-dependant apoptosis in MCF-7 cells which was correlated with the resulting cytotoxicity in rat insulinoma cells (INS-1E), which have high levels of intracellular GSH. [16] Inspired by the high affinity of thiols, such as GSH, for gold as exemplified by Che's seminal work on switch-on fluorescent probes [17] and the reported anion transport activity of 1,3bis(benzimidazol-2-yl)benzenes [18] and similar motifs [19] , we adapted Che's systems and designed and synthesized new switchable cycloaurated putative anion transporters based on the structurally related 1,3-bis(benzimidazol-2-yl)pyrimidine (BisBzImPy).…”
Section: Introductionmentioning
confidence: 90%
“…The level of GSH in many kinds of solid tumor tissues was much higher than that in normal tissues and can be over 1000-fold higher than in blood [1,2]. The elevated GSH level helps to prevent apoptosis of cancer cells by detoxifying reactive oxygen species (ROS) [3] and induce chemotherapeutic drugs resistance through GSH spontaneous reactions or xenobiotics reactions catalyzed by GSH S-transferase (GST) [4,5]. GSH regulation strategies mainly include the depletion of existing intracellular GSH and the inhibition of GSH biosynthesis.…”
Section: Introductionmentioning
confidence: 99%